2013
DOI: 10.11118/actaun201361030803
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of fruit juices by NIR spectroscopy

Abstract: AbstractŠNURKOVIČ PETR: Quality assessment of fruit juices by NIR spectroscopy. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013, LXI, No. 3, pp. 803-812

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…By training the models with a broader range of spectral information, the variations attributed to sample preparation and Vis-NIRs analysis would be mitigated. It should be noted that there are studies based on spectroscopy data in which better results were obtained with PLS than with SVR [ 53 ], while in other cases, the opposite is reported [ 54 ] or even similar performances [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…By training the models with a broader range of spectral information, the variations attributed to sample preparation and Vis-NIRs analysis would be mitigated. It should be noted that there are studies based on spectroscopy data in which better results were obtained with PLS than with SVR [ 53 ], while in other cases, the opposite is reported [ 54 ] or even similar performances [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…By using radial basis function neural network classifiers, the authors acquired a classification accuracy of 97.62%. Šnurkovič [ 62 ] demonstrated discrimination between a mixture of various juices that were adulterated with water, sugar, and fruit juices which was based on NIR spectral data. Several other investigators reported that infrared spectroscopy, specifically the MIR spectral region, has successfully been applied for authentication and adulteration testing [ 14 , 58 , 63 ].…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…This technique has previously been used to detect the addition of sugars in apple juice [ 21 ] and bayberry juice [ 26 ]. Additionally, it has been successfully used to determine the quality of juice from different fruits [ 27 ], as well as to determine the addition of water in bayberry juice [ 28 ] and for the detection of adulterations in lime juice [ 29 ]. However, to the best of the authors’ knowledge, this technique has not been previously used to detect and quantify juice-to-juice adulterations.…”
Section: Introductionmentioning
confidence: 99%